Energy-positive green space: Designing carbon-neutral community architecture in edge environments - Wai Yan Oo (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Urban edge zones—the transitional areas between dense urban cores and peri-urban landscapes—often face rapid development pressure, environmental vulnerability, and uneven access to public space. Although energy-positive and carbon-neutral design strategies are increasingly discussed, their integration with participatory placemaking remains underexamined, particularly at community scale in edge contexts. Methods: This study adopts a qualitative design-research case study in Amsterdam Noord, combining site-based environmental observation (e.g., solar exposure, wind behavior, vegetation, and use patterns) with iterative participatory co-design workshops. The architectural proposal was developed through low-tech, human-centered methods, emphasizing passive design optimization, low-embodied-carbon material strategies, and on-site renewable energy integration. Findings: Community input consistently prioritized shaded gathering areas, accessible green space, edible gardens, ecological pathways, and flexible multipurpose zones, which directly shaped spatial organization and environmental strategies. The proposed community green structure achieved a projected 12% operational energy surplus through integrated passive measures and photovoltaic-based generation. Survey findings further indicated high satisfaction with the co-design process, strong recognition of environmental friendliness, increased sustainability awareness, and broad support for applying similar participatory approaches in future projects. Conclusion: This study suggest that energy-positive, carbon-neutral community architecture can be effectively developed in urban edge environments when environmental logic is embedded within participatory, context-sensitive placemaking. This integrated approach supports both measurable environmental performance and social outcomes such as ownership, trust, and long-term stewardship. Novelty/Originality of this article: This research contributes a replicable participatory design model for energy-positive green-space architecture tailored to urban edge conditions, demonstrating how technical sustainability goals can be advanced together with community-led placemaking outcomes.